Strengthening women’s livelihoods through the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA): Policy strategies for resilience and inclusion: The Bhubaneshwar Charter - Narayanan, Sudha; Raghunathan, Kalyani; Kosec, Katrina; Paul, Meekha Hannah; Kumar, Deepak; Agnihotri, Satish B.; Murthy, Indu K.; Sarathy, Partha; Panda, Aditi; Kyle, Jordan (International Food Policy Research Institute, 2025)
Globally, there is increasing recognition of the significant potential for social protection programs to sup-port sustainable livelihoods and build household resilience to climatic and economic shocks (Jordan et al., 2021; Norton et al., 2020). For women—who disproportionately bear the burden of these shocks—such programs serve as a critical safety net and a pathway to economic empowerment (Kosec et al., 2023; Mason & Agan, 2015). Yet, the extent to which social protection delivers on this promise depends on robust financing, inclusive program design, and effective implementation. Evidence suggests that public interventions often fall short in addressing gender inequalities, and that complementary efforts must be made to redress entrenched disadvantages that women might face in shaping, accessing, and benefiting from these programs.